Modelling the Kinetics of Biogas Production from Mesophilic Anaerobic Co-Digestion of Cow Dung with Plantain Peels - Ganiyu Kayode Latinwo; Samuel Enahoro Agarry (Center of Biomass & Renewable Energy (CBIORE), 2015)
This work investigated the effect of plantain peels as co-substrate in the anaerobic digestion of cow dung for efficient and high biogas production. The biogas experiments were carried out in two different 5 L anaerobic digesters and incubated for 40 days at ambient mesophilic temperatures (28 oC to 34 °C). The results showed that co-digestion of cow dung with plantain peels as co-substrate reduced start-up time for biogas generation and increased biogas yield by 18% as compared to cow dung alone. Peak biogas production was obtained for both digesters at pH of 6.7 and 6.9 as well as temperature of 29 and 30oC, respectively. Modelling study revealed that exponential plot simulated better in both ascending and descending limb than the linear plot the biogas production rates in biogas production from cow dung co-digested with plantain peels and cow dung alone, respectively. Logistic growth model and modified Gompertz plot showed better correlation of cumulative biogas production than exponential rise to maximum plot. These results show that biogas production can be enhanced efficiently through co-digestion process.